2021
DOI: 10.21037/tau-20-1153
|View full text |Cite
|
Sign up to set email alerts
|

Trifecta outcomes of modified robot-assisted simple enucleation and standard robot-assisted partial nephrectomy for treating clinical T1b renal cell carcinoma

Abstract: Background: To compare perioperative outcomes and Trifecta achievement of modified robot-assisted simple enucleation (MRASE) with robot-assisted partial nephrectomy (RAPN) for treating clinical T1b renal tumors. Methods: We analyzed 203 patients who underwent MRASE or RAPN for clinical T1b renal tumors at our institution from September 2014 to June 2018. The two groups were compared regarding perioperative outcome variables. Trifecta was defined as no perioperative complications, negative surgical margin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 35 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…Fifteen of the 17 studies were published in English; the other 2 were published in Spanish [ 40 ] and Russian [ 41 ], respectively. The countries of origins of the included studies were China [ 42 43 44 45 46 ], Japan [ 47 48 ], Italy [ 49 50 ], Spain [ 40 ], Romania [ 51 52 ], Russia [ 41 ], and the United States [ 53 54 55 56 ]. We attempted to contact the corresponding authors of the included studies to obtain additional information on the study methodology and results and received replies for two studies [ 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen of the 17 studies were published in English; the other 2 were published in Spanish [ 40 ] and Russian [ 41 ], respectively. The countries of origins of the included studies were China [ 42 43 44 45 46 ], Japan [ 47 48 ], Italy [ 49 50 ], Spain [ 40 ], Romania [ 51 52 ], Russia [ 41 ], and the United States [ 53 54 55 56 ]. We attempted to contact the corresponding authors of the included studies to obtain additional information on the study methodology and results and received replies for two studies [ 53 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean (or median) duration of warm ischemia ranged from 4 to 27 minutes. The residual renal function measured by GFR was reported perioperatively [ 43 48 52 55 ], within 3 months of surgery [ 43 47 ], and at 3 months after surgery [ 43 45 48 51 ]. Two NRSs reported cancer-specific mortality (follow-up: median 18 to 37 months), but no study reported overall mortality [ 42 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations